Answer: 8n
Let's simplify step-by-step.
(2(n+1)−1)2−(2n−1)2
Distribute:
=4n2+4n+1+−4n2+4n+−1
Combine Like Terms:
=4n2+4n+1+−4n2+4n+−1
=(4n2+−4n2)+(4n+4n)+(1+−1)
=8n
The value of y-x is (-3)
<u>Solution:</u>
Given: The value of x-y=3
To find: The value of y-x
![\bold{x-y=3\rightarrow (1)}](https://tex.z-dn.net/?f=%5Cbold%7Bx-y%3D3%5Crightarrow%20%281%29%7D)
Let's multiply the equation (1) by (- 1) on both sides,
![\Rightarrow\bold{(x - y)\times(- 1) = 3\times(- 1)}](https://tex.z-dn.net/?f=%5CRightarrow%5Cbold%7B%28x%20-%20y%29%5Ctimes%28-%201%29%20%3D%203%5Ctimes%28-%201%29%7D)
![\Rightarrow\bold{-(x-y)=-3}](https://tex.z-dn.net/?f=%5CRightarrow%5Cbold%7B-%28x-y%29%3D-3%7D)
On multiplying the sign,
![\Rightarrow\bold{(-x+y)=-3}](https://tex.z-dn.net/?f=%5CRightarrow%5Cbold%7B%28-x%2By%29%3D-3%7D)
The above equation can also be written as,
![\Rightarrow\bold{y-x=-3\rightarrow \text{(The required equation)}}](https://tex.z-dn.net/?f=%5CRightarrow%5Cbold%7By-x%3D-3%5Crightarrow%20%5Ctext%7B%28The%20required%20equation%29%7D%7D)
<u>Multiplication of signs:</u>
![\Rightarrow( + )\times( + ) = ( + )](https://tex.z-dn.net/?f=%5CRightarrow%28%20%2B%20%29%5Ctimes%28%20%2B%20%29%20%3D%20%28%20%2B%20%29)
![\Rightarrow( + )\times( - ) = ( - )](https://tex.z-dn.net/?f=%5CRightarrow%28%20%2B%20%29%5Ctimes%28%20-%20%29%20%3D%20%28%20-%20%29)
![\Rightarrow( - )\times( + ) = ( - )](https://tex.z-dn.net/?f=%5CRightarrow%28%20-%20%29%5Ctimes%28%20%2B%20%29%20%3D%20%28%20-%20%29)
![\Rightarrow( - )\times( - ) = ( + )](https://tex.z-dn.net/?f=%5CRightarrow%28%20-%20%29%5Ctimes%28%20-%20%29%20%3D%20%28%20%2B%20%29)
In simpler terms, when we multiply two integers with the same signs, the result is always positive and when we multiply two integers with different signs, the result is always negative.
Answer:
It is an obtuse angle!
Step-by-step explanation: